The Effect of Educational Video on The Knowledge Level of Chemotherapy Side Effect and Its Management on Patient Undergoing Chemotherapy in Gatot Soebroto Jakarta Hospital - Ni Made Diah Pusparini Pendet; Muhlisoh; Dewi Irawati; Riri Maria (Proceeding of International Conference on Science, Health, And Technology, 2019)
Knowledge about chemotherapy side effects plays a significant role in cancer patient compliance with the regimen of chemotherapy. Educational video is a media that can be used to increase the level of knowledge of chemotherapy side effects on the cancer patient. This study aimed to know the effect of educational video on the level of knowledge of chemotherapy side effects on cancer patients undergoing chemotherapy in Gatot Soebroto Jakarta Hospital. This was an innovation project which involved 11 cancer patients in Gatot Soebroto Hospital. Statistical analysis using Wilcoxon-Test showed that there was a significant difference in the level of knowledge’s score before and after using the educational video (p = 0.006). Based on the result, we concluded that educational videos could increase the level of knowledge about the side effects of chemotherapy. We suggest using educational video as a media to provide information about chemotherapy in a health education program on cancer patients. Further study using a larger sample size and longer duration of study is needed to be conducted.